A novel ROS-activable self-immolative prodrug for tumor-specific amplification of oxidative stress and enhancing chemotherapy of mitoxantrone. (February 2023) - Zhang, Hongjie; Chen, Weijian; Wang, Jing; Du, Wenxiang; Wang, Bibo; Song, Lei; Hu, Yuan; Ma, Xiaopeng
Abstract: Reactive oxygen species (ROS) as well-known endogenous stimuli has been widely used to activate drug delivery systems (DDSs) for tumor-specific therapy. Unfortunately, endogenous ROS in the tumor microenvironment (TME) is not enough to achieve effective therapeutic efficacy and cancer cells have adapted to high oxidative stress by upregulating glutathione (GSH) level. Herein, we devised a novel ROS-activable self-immolative prodrug CASDB with both GSH-depletion ability and ROS self-supply competence. Then, an stimuli-responsive nanoplatform integrating CASDB with clinical chemotherapeutics mitoxantrone (MTO) and PLGA was fabricated (denoted as CMPs) through nanoprecipitation method. The CMPs could achieve desired accumulation at tumor tissues through enhanced permeability and retention (EPR) effects. Then the accumulated CMPs could induce tumor cell apoptosis efficiently. Especially, ROS in tumor sites could trigger the immolation of CASDB to generate CA and quinone methide (QM). Then CA and QM cooperatively promoted damage of mitochondria due to oxidative stress and led to cancer cells more sensitive to MTO. Accordingly, MTO could perturb cellular microenvironment of cancer cells then promote the degradation of CASDB. The experiment results demonstrated that CMPs were ideal for desirable synergetic tumor-specific anticancer therapy with negligible systemic toxicity. The half-maximal inhibitory concentrations (IC50) value of CMPs was 6.53 μM, while the IC50 values of MTO was 14.76 μM. And the CMPs group showed the strongest tumor suppressor effect with the tumor sizes increased to 1.2-fold (Control group: 20.6-fold, MTO only: 3.0-fold). This study should be inspirational for designing efficient prodrugs to overcome the handicaps of traditional chemotherapy.